Long-term degradation, damage and fracture in deep rock tunnels: A review on the effect of excavation methods (Fracture and Structural Integrity, 2021)
Rocks are frequently host materials for underground structures, particularly for deep Tunnels. Their behavior plays a fundamental role in the overall stability of these structures. In fact, the erection of deep tunnels imposes rocks excavations around the defined routes. These excavations are generally carried out by various methods of which the most used are Drill-and-Blast (DB) and Tunnel Boring Machine (TBM).  However, regardless of the tunnelling method used, the impacts such as the perturbation of the initial stress field in rocks and the release of the stored energy are always significant. The impacts produce damage, fractures and deformations which are generally time-dependent and influence the long-term stability of deep tunnels built in rocks. Thus, by considering the aforementioned excavation methods, this paper identifies, reviews and describes the relevant factors generated during and after rock excavations. Interestingly, such factors directly or indirectly influence the long-term stability and therefore the structural integrity of deep rock tunnels. In addition, some recommendations and proposals for future works are presented. This paper can provide useful references in understanding the degradations, damage and fractures generated by tunnelling methods and facilitate suitable actions to ensure long-term stability of deep underground structures.
Keywords: Excavation methods; Excavation impacts; Rocks behavior; Deep Tunnels; Long-term Stability